Design and Implementation of 13 Level Multilevel Inverter With Reduced THD Level - Ms. Jitha Varghese, Dr. P. Deiva Sundari , Mr. S. Gowtham (International Journal of Advanced Science and Technology, 2020)
This paper proposes the modelling and simulation of 13-level multilevel inverter (MLI) with a modernized Pulse Width Modulation (PWM) technique. MLI is one of the most efficient power converter which are especially suited for high power applications with reduced harmonics. This paper primarily focuses on generating high level inverter output with optimal number of switches. The method used to trigger the switch for output voltage level control  is fundamental frequency switching method. This proposed PWM technique applied to cascaded MLI results in reduced percentage of THD. The performance evaluation of the proposed 13-level cascaded MLI  is verified  with MATLAB / Simulink model